Fracture of Parallel Strand Bamboo Composite under Mode I Loading: DCB Test Investigation - Yurong Shen; Dongsheng Huang; Ying Hei Chui; Chunping Dai (Advances in Materials Science and Engineering)
This paper describes the experimental studies on Mode I fracture of parallel strand bamboo (PSB) by the double cantilever beam (DCB) test. R-curves based on the elementary beam theory and specimen compliance are proposed in order to overcome the difficulties to monitor the crack propagation during experiments. The results demonstrate that the energy release rate (ERR) is influenced by the specimen geometry, i.e., the specimen width and initial crack length. The ERR at the plateau level is similar for the range of the analyzed widths (B = 20, 40, and 60 mm), while it decreases with width increasing up to 80 mm and 100 mm. The energy release rate for PSB specimens would verge to a stable value with the width increasing up to a specific value, while the value of the energy release rate will be influenced by the initial crack length. Consequently, the DCB tests also show that the obtained R-curve in this study is not a material property.